(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This research explores the presence and contributions of foreign university branches in Uzbekistan to the development of the educational system. It aims to provide an overview of the establishment and operations of foreign university branches, assess their impact on the quality of education in Uzbekistan, and identify the key areas in which they have contributed to the development of the educational system. The study draws on a combination of primary and secondary data, including interviews, surveys, and academic literature. The findings highlight the positive effects of foreign university branches on curriculum development, faculty training, research collaboration, and internationalization efforts. The research concludes by emphasizing the importance of continued collaboration between foreign university branches and local institutions for sustained educational development in Uzbekistan.